TRAMWAY MANAGEMENT SYSTEM IN INDONESIA - , MELIA DAMAYANTI, Prof. Dr. Ir. Siti Malkhamah, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tramway systems, which can carry more passengers than buses at one haul, are now being proposed to meet Indonesiaâs public transport requirement. In order to develop successful tramway systems, Indonesia needs to learn from other countriesâ experiences. The object of this thesis is to analyse the management structures for operating trams in different countries and then propose a suitable organisational structure for operating trams, if re-introduced, in Indonesia. The author chose France (Montpellier tramway), Germany (Karlsruhe tram-train) and the UK (Nottingham Express Transit) as the role model countries for investigation. Additional material is also sourced from the literature. From the analysis, the author then proposes the most appropriate organisational structure for implementation in Indonesia. Based on the findings from the case studies for both construction and ongoing operation, the author proposes the most suitable tramway management structure for operating tramways in Indonesia would be one similar to that in Montpellier, but with some up-front funding from non-government sources as with NET (Nottingham Express Transit). The key features of the proposal are: Establishment of a public transport company by local government to manage all public transport systems in a particular area